2018
DOI: 10.1186/s12984-018-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the grasping intention from electromyography during reaching motions

Abstract: BackgroundActive upper-limb prostheses are used to restore important hand functionalities, such as grasping. In conventional approaches, a pattern recognition system is trained over a number of static grasping gestures. However, training a classifier in a static position results in lower classification accuracy when performing dynamic motions, such as reach-to-grasp. We propose an electromyography-based learning approach that decodes the grasping intention during the reaching motion, leading to a faster and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…Once they had executed the desired grip, they were required to perform a dynamic movement, thus covering with their (residual) arm the region of interest. This approach was followed because it has been previously shown that it can help alleviate the limb position effect [31] and improve decoding performance [14], [15]. One of the amputee participants performed bilateral mirrored movements as they found it was easier in that way to perform phantom limb muscle activations.…”
Section: Behavioural Taskmentioning
confidence: 99%
“…Once they had executed the desired grip, they were required to perform a dynamic movement, thus covering with their (residual) arm the region of interest. This approach was followed because it has been previously shown that it can help alleviate the limb position effect [31] and improve decoding performance [14], [15]. One of the amputee participants performed bilateral mirrored movements as they found it was easier in that way to perform phantom limb muscle activations.…”
Section: Behavioural Taskmentioning
confidence: 99%
“…Dynamic 3D space experiments involve the transition between shoulder, elbow, and wrist joint angles while eliciting a target motion class [22,[143][144][145][146][147][148]. Generally, these protocols can be grouped into two subsets: reach-to-grasp, and activities of daily living (ADLs).…”
Section: Dynamic 3d Spacementioning
confidence: 99%
“…The further development of assistive and training devices for persons with impaired hand function will probably also include other command systems than those used in the current version of the SEM Glove. Electromyography is already used in some exoskeletons, in refined prostheses for amputees, and in the development of a soft orthosis (42,43), and brainmachine interfaces may open new opportunities.…”
Section: "Well Yes It´s the Fine Hand Use That's My Problem But Itmentioning
confidence: 99%